Acute Respiratory Distress Syndrome - Chiumello, Davide (Springer International Publishing : Imprint: Springer, 2017)
This book covers all clinical aspects of acute respiratory distress syndrome (ARDS), from definition to treatment, focusing on the more recent recommendations and evidence-based medicine. The addressed topics are the various ventilation strategies, the impact of prone positioning, the use of partial and total extracorporeal support, the value of vasodilators, the weaning from mechanical ventilation, the pharmacological interventions, noninvasive ventilation, and the strategies using anti-inflammatory agents and stem cells. Furthermore, different related topics are also discussed, such as lung imaging, sedation, metabolic support, and hemodynamic instability. A concluding chapter specifically addresses ARDS in children. This up-to-date volume, written by experts in the field, will be of value for all health care practitioners seeking state of the art on the management of patients with this complex syndrome.
Keywords: Medicine.; Anesthesiology.; Emergency medicine.; Critical care medicine.; elektronické knihy; electronic books